Design, Synthesis, and Biological Evaluation of Thiazolidine‐2, 4‐dione Conjugates as PPAR‐γ Agonists. Issue 6 (21st April 2015) - Nazreen, Syed; Alam, Mohammad Sarwar; Hamid, Hinna; Yar, Mohammad Shahar; Dhulap, Abhijeet; Alam, Perwez; Pasha, Mohammad Abdul Qadar; Bano, Sameena; Alam, Mohammad Mahboob; Haider, Saqlain; Kharbanda, Chetna; Ali, Yakub; et al.
<x xml:space="preserve">Abstract</x> A library of synthesized conjugates of phenoxy acetic acid and thiazolidinedione 5a–m showed potent peroxisome proliferator activated receptor‐γ (PPAR‐γ) transactivation as well as significant blood glucose lowering effect comparable to the standard drugs pioglitazone and rosiglitazone. Most of the compounds showed higher docking scores than the standard drug rosiglitazone in the molecular docking study. Compounds 5l and 5m exhibited PPAR‐γ transactivation of 54.21 and 55.41%, respectively, in comparison to the standard drugs pioglitazone and rosiglitazone, which showed 65.94 and 82.21% activation, respectively. Compounds 5l and 5m significantly lowered the blood glucose level of STZ‐induced diabetic rats. Compounds 5l and 5m lowered the AST, ALT, and ALP levels more than the standard drug pioglitazone. PPAR‐γ gene expression was significantly increased by compound 5m (2.00‐fold) in comparison to the standard drugs pioglitazone (1.5‐fold) and rosiglitazone (1.0‐fold). Compounds 5l and 5m did not cause any damage to the liver and could be considered as promising candidates for the development of new antidiabetic agents.